Recommendations for online learning challenges in nursing education during the COVID-19 pandemic - Boitumelo J. Molato; Leepile A. Sehularo (AOSIS, 2022)
Background: Nursing education institutions have had to change from face-to-face to online learning because of the coronavirus disease 2019 (COVID-19) pandemic. The online learning mode, however, had several challenges. Objectives: To explore and describe recommendations made to address the online learning challenges in nursing education during the COVID-19 pandemic. Method: This study adopted a narrative literature review to achieve its objectives. The search for the relevant literature used Google Scholar, ScienceDirect, African Journal (previously SAePublications), EBSCOhost, EBSCO Discovery Service and Scopus databases. Results: There were four findings identified from the literature search: provision of adequate resources, monitoring of academic dishonesty, provision of technical support and revision of the curriculum. Conclusion: More work in nursing education is necessary to address the challenges of adopting online learning during and after the COVID-19 pandemic. To meet the issues of online learning in nursing education, thorough preparations and safeguards are necessary. Contribution: The outcomes of this study will benefit nursing education by incorporating recommendations from many studies to overcome online learning issues in nursing education during the COVID-19 pandemic.